On the right track? The role of work experience in migrant mothers' current employment probability - Christina Boll; Andreas Lagemann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2021)
This paper investigates the role of work experience in migrant mothers' current employment in Germany. Unlike previous papers, we focus on actual experience and add the motherhood aspect. To this end, we use data from the German Socio-Economic Panel 2013-2018 including the IAB-SOEP Migration Sample. Having immigrated to Germany and female sex are the two treatments of our sample of 491 migrant mothers, with 7,077 native mothers and 1,383 migrant fathers serving as control groups. Running LPM with individual FE and testing the robustness of the work experience estimators against a range of covariates and unobserved time-varying confounders with Oster bounds, we show that years of domestic part-time experience yield higher returns for migrant mothers compared to migrant fathers and non-migrant mothers. We conclude that current employment is significantly fueled by former employment; thus policies should be designed such that they help women to 'get on the right track'.
Keywords: J61; J16; J24; 330; migrant employment; maternal employment; LPM with individual FE; Oster test; actual work experience